Glyphosate, trinexapac-ethyl, and mepiquat chloride on the productive performance of bush snap beans - Guilherme Renato Gomes (Semina: Ciências Agrárias, 2018)
Studies aimed at improving production and yield of bush snap beans are desirable; the results may provide growers with new techniques to improve profitability. In the literature, there are few reports on the productive performance of vegetables subjected to doses of glyphosate and plant regulators. Thus, this study aimed to evaluate the effect of glyphosate, trinexapac-ethyl, and mepiquat chloride doses on the production components and yield of bush snap beans. We tested various doses: a) glyphosate: 0.0; 18.0; 36.0; 72.0; and 144.0 g acid equivalent (ae) ha-1; b) trinexapac-ethyl: 0.0; 62.5; 125.0; 250.0; and 500.0 g ae ha-1; and c) mepiquat chloride: 0.0; 25.0; 50.0; 75.0; and 100.0 g ae ha-1. The experimental design was completely randomized, with four replications per treatment. We evaluated plant height, stem diameter, number and mass of pods per plant, mass, length, and diameter of pod, and yield. The analysis of variance was conducted by applying the F test, and the doses were submitted to regression analysis (p < 0.05). Each active ingredient was considered separately. Productive performance was favored by using doses up to 16.0 g ae ha-1 of glyphosate, showing increased pod mass per plant and yield. As trinexapac-ethyl doses increased, the number of pods per plant decreased but mean pod mass increased. Doses of mepiquat chloride up to 59.5 g ae ha-1 increased mean pod mass. Finally, pod yield was not influenced by trinexapac-ethyl and mepiquat chloride.